Gene–Environment Interactions—What Can These Tell Us about the Relationship between Asthma and Allergy? - Turner, Steve (Frontiers in Pediatrics, 2017)
Asthma is a common condition which is associated with atopy and allergic conditions including hayfever, eczema and food allergies. Asthma and atopy are both complex conditions where genetic and environmental factors are implicated in causation. Interactions between genetic and environmental factors, likely via epigenetic mechanisms, are widely thought to be important in determining the risk for developing asthma and atopy. The nature of the relationship between asthma and atopy is unclear and the answer to the question “does atopy cause asthma?” remains unknown. This review explores the relationship between asthma and atopy from a gene-environment interaction perspective and tackles the question “are similar gene-environment interactions present for asthma and atopy?” The main finding is that gene-environment interactions are described for asthma and atopy in children but these interactions are seldom sought for both asthma and atopy in the same population. In the few instances where a gene-environment interaction is sought in relation to both asthma and atopy, there is no consistent evidence of interactions common to both asthma and atopy. Many plausible gene-environment interactions for asthma and atopy are yet to be explored. Overall, from the gene-environment interaction perspective, there is absence of evidence to help understand the complex relationship between asthma and atopy.